Online education in times of pandemic: the opinion of college students related to the challenges founds (Research, Society and Development, 2021)
Due to the COVID-19 pandemic and the need for social isolation, face-to-face teaching was replaced by online education at universities. Thus, this article aims to know the environment in which students are inserted during remote classes and analyze the opinion of these academics about the effects of the pandemic on their daily learning. Therefore, an online questionnaire through Microsoft Forms was applied to students regularly enrolled in the Computer Engineering course at UEMG.  The results show that the most difficulties found by students during online classes were adaptation to remote classes, and psychological factors. Although the internet is weakness during teaching, according to the response of these students, emotional factors were more relevant in this period. The analysis of the data obtained from the questionnaires applied showed that although adequate platforms for online teaching, as well as a good internet connection, are essential for remote classes to take place, emotional factors arising from social isolation, adaptation to classes and the study environment were those that most disturbed learning process of the students during the pandemic time.